Alumina supported oxide based catalysts for methanation reaction - Hazwan Faiz Abd. Rahim, 1987-; Wan Azelee Wan Abu Bakar; Fakulti Sains (2009)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2009